Metacognitive Strategies in Reading Instruction for German Language Learners– a Literature Review - Dewi Kartika; Primardiana Hermilia Wijayati; Dudy Syafruddin; Abdul Kasim Achmad (Proceeding of International Conference on Education, Language, Literacies, and Literary Studies (ICONELS), 2025)
This literature review investigates the use of metacognitive strategies—planning, monitoring, and evaluating—to support reading comprehension among B1-level learners of German as a Foreign Language (GFL). In the Indonesian educational context, limited exposure to authentic German texts and linguistic differences often hinder learners’ ability to understand complex written materials. Metacognitive strategies offer a structured approach to help learners manage their reading processes, build autonomy, and engage more deeply with texts. The review highlights how these strategies can be integrated into reading instruction through pre-reading (goal setting and text prediction), while-reading (clarifying and self-questioning), and post-reading (reflection and summarization) activities. However, the implementation of metacognitive instruction faces challenges, including low student awareness, limited teacher preparation, and a strong focus on exam-based outcomes in classrooms. To overcome these barriers, the paper advocates for sustained, explicit instruction and teacher training that embeds strategic reading into regular classroom practice. It also calls for curriculum and assessment reforms that value process-oriented reading. Ultimately, fostering metacognitive awareness equips learners not only to improve comprehension but also to become more self-regulated, reflective, and confident language users in the long term.